2021
DOI: 10.7717/peerj-cs.589
|View full text |Cite
|
Sign up to set email alerts
|

An efficient filter with low memory usage for multimedia data of industrial Internet of Things

Abstract: One of the essential concerns of Internet of Things (IoT) is in industrial systems or data architecture to support the evolutions in transportation and logistics. Considering the Industrial IoT (IIoT) openness, the need for accessibility, availability, and searching of data has rapidly increased. The primary purpose of this research is to propose an Efficient Two-Dimensional Filter (ETDF) to store multimedia data of IIoT applications in a specific format to achieve faster response and dynamic updating. This fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To face the noise data problem, a reasonable data filter is needed to increase the training efficiency of network models, which is one of the important aspects of network model training. Data filters play an important role when dealing with large-scale datasets with a large number of samples and features ( Toet, 2016 ; Goudarzi & Rahmani, 2021 ; Li, Yang & Wen, 2021 ). We found that the noise data can be filtered from both the current and the historical perspectives of the noise data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To face the noise data problem, a reasonable data filter is needed to increase the training efficiency of network models, which is one of the important aspects of network model training. Data filters play an important role when dealing with large-scale datasets with a large number of samples and features ( Toet, 2016 ; Goudarzi & Rahmani, 2021 ; Li, Yang & Wen, 2021 ). We found that the noise data can be filtered from both the current and the historical perspectives of the noise data.…”
Section: Literature Reviewmentioning
confidence: 99%